2022
DOI: 10.3390/cancers14215470
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Patient-Reported Outcome Screening on the Survival of People with Cancer: A Systematic Review and Meta-Analysis

Abstract: This study examined the effects of the routine assessment of patient-reported outcomes (PROs) on the overall survival of adult patients with cancer. We included clinical trials and observational studies with a control group that compared PRO monitoring interventions in cancer clinical practice to usual care. The Cochrane risk-of-bias tools were used. In total, six studies were included in the systematic review: two randomized trials, one population-based retrospectively matched cohort study, two pre–post with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Electronic patient-reported outcomes (ePROs) are an evidence-based means of detecting cancer symptoms and treatment side effects earlier and improving patient outcomes. Studies have demonstrated the benefits of ePRO symptom monitoring between clinic visits, including improved symptom control, 1-5 physical function, 6-8 treatment adherence, 5-10 patient satisfaction, 4,8,10 patient self-efficacy, 3,7 cost-effectiveness, 11,12 and overall survival, 13-16 as well as reductions in emergency department presentations 5,6,10,15,17-19 and hospital admissions. 15,19 ePRO symptom monitoring is recommended by the European Society of Medical Oncology Clinical Practice Guidelines 20 and as part of value-based health care initiatives in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic patient-reported outcomes (ePROs) are an evidence-based means of detecting cancer symptoms and treatment side effects earlier and improving patient outcomes. Studies have demonstrated the benefits of ePRO symptom monitoring between clinic visits, including improved symptom control, 1-5 physical function, 6-8 treatment adherence, 5-10 patient satisfaction, 4,8,10 patient self-efficacy, 3,7 cost-effectiveness, 11,12 and overall survival, 13-16 as well as reductions in emergency department presentations 5,6,10,15,17-19 and hospital admissions. 15,19 ePRO symptom monitoring is recommended by the European Society of Medical Oncology Clinical Practice Guidelines 20 and as part of value-based health care initiatives in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…PRO-based symptom management interventions typically consist of collecting patient symptom reports using ePRO tools and responding to these reports, which serve as measurement methods and digital interventions to monitor, detect, and manage patients’ symptoms, thereby improving their outcomes [ 16 ]. Recent evidence suggests that, compared to standard care, symptom management strategies based on ePRO could enhance the symptom burden, quality of life and overall survival of patients with cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade there has been growing interest in the use of PROMS in oncology clinical care as their routine collection has been associated with improved survival, reduced hospitalisations and emergency department presentations [ 6 9 ]. Further, with improved cancer treatments, the number of cancer survivors has increased [ 10 , 11 ]. Positive findings from a systematic review by Graupner and colleagues recommend the use of PROMs in daily cancer care combined with feedback to the patients and relevant stakeholders [ 10 ] which may provide an important opportunity for a standardised approach to personalised cancer care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%